Routledge handbook of South Asian criminology - Jaishankar, K. (Routledge handbooks, 2020)
Crime and criminal justice processes -- Afghanistan: state and non-state oriented criminal justice systems -- Bangladesh : issues and introspections on crime and criminal justice -- Bhutan : penal laws, crimes and criminal justice processes -- India : a historical perspective of criminal justice system -- Maldives : towards the reformation of criminal justice system -- Nepal : institutions in the criminal justice system and the need for reforms -- Pakistan : criminal justice processes and issues of crime, policing, judiciary, and prisons -- Sri Lanka : criminal justice system and rule of law -- Historical perspectives of crime and justice -- Criminal justice tenets in manusmriti : a critical appraisal of the Ancient Indian Hindu Code -- Witchcraft accusation, victimization and demonology in Nepal -- Crime and justice in ancient South India (Sangam age) : gleanings from Tamil literature -- Goondas of Calcutta : crimes and policing in the colonial India -- Opium production in India, Pakistan and Afghanistan : historical milieu and counter measures -- Homicide in ancient, medieval, British and contemporary India -- Politics of crime and justice -- Terror and trafficking in Afghanistan, Pakistan and India : a routine activity approach -- War, crime, justice and social order in Afghanistan -- Organised crime, gangs and the complexity of group offending in Bangladesh -- War crimes in Sri Lanka -- Madaris and suicide terrorism in Pakistan : is there an association? -- Post-conflict crime and violence in Nepal : trends, dynamics and drivers -- Religious terrorism in Bangladesh : patterns, trends and causes -- Crime and justice policies -- Human trafficking in South Asia : regional cooperation and responses -- Religious, societal reflection and rights of transgender in India -- Transitional justice processes in Bangladesh -- "Nirbhaya incident" and juvenile justice policies in India : a situational analysis -- Crime among young offenders in Bhutan : trends, factors and determinants -- Victims and victimization -- Women victims of war and crime in Afghanistan -- Human trafficking in Nepal : a victimological perspective -- Political crime victimization in Bangladesh -- Traditional practices and victimization of women in Nepal : the case of Chhaupadi -- Rohingyas in Myanmar and Bangladesh : an examination of collective and secondary victimization -- Conclusion.